Nonconventional chemicals and methods of application for management of purple blotch of onion under field condition - Behera, Srujani; Mahapatra, Sunita; Das, Srikanta (Indian Journal of Plant Protection, 2020)
A field experiment was carried out for two consecutive years (2011-12 and 2012-13) in Rabi season at University Research Farm, Kalyani, Nadia, W.B. Six non-conventional chemicals were applied in three different methods to determine their effect on disease severity of purple blotch of onion and bulb yield. The disease severity was minimum and bulb yield was maximum with combined application of salicylic acid @ 10-5 M as root dipping and foliar spray followed by only root dipping with same inducer chemical. So, only root dipping at the time of transplanting at very low concentration of non-conventional inducer chemical provide strong and lasting protection against the destructive disease purple blotch and increase bulb yield.